2001
DOI: 10.1002/1521-3765(20010119)7:2<436::aid-chem436>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Stirring Effects on the Spontaneous Formation of Chirality in the Homoassociation of Diprotonatedmeso-Tetraphenylsulfonato Porphyrins

Abstract: Homoassociates of the achiral title porphyrins in acid solutions show spontaneous symmetry breaking, which can be detected by circular dichroism (CD). The CD spectra are due to differential scattering and differential absorption contributions, the relative significance of which is related to the shape and size of the homoassociate. When an earlier model, designed for the association of these diprotonated porphyrins (J aggregates with the geometry of stepped sheets of intramolecularstabilised zwitterions), was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 58 publications
6
83
0
Order By: Relevance
“…Various spectroscopic methods have been applied to define electronic structure [14][15][16][17][18] and exciton dynamics [19][20][21][22] in TPPS 4 aggregates. Recent investigation of TPPS 4 J-aggregates in polyvinyl-alcohol by means of electroabsorption spectroscopy suggested that excitons in these structures are coherently delocalised over 60-80 monomer molecules [23].…”
Section: Introductionmentioning
confidence: 99%
“…Various spectroscopic methods have been applied to define electronic structure [14][15][16][17][18] and exciton dynamics [19][20][21][22] in TPPS 4 aggregates. Recent investigation of TPPS 4 J-aggregates in polyvinyl-alcohol by means of electroabsorption spectroscopy suggested that excitons in these structures are coherently delocalised over 60-80 monomer molecules [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that TPPS aggregates are easily induced to show CD activity by achiral molecules or even by mechanical stirring. 31 The chirality of TPPS aggregates is normally attributed to the helical formation of the TPPS aggregates due to the broken of the mirror-symmetry of the diprotonated porphyrins in the TPPS aggregates or the formation of a 90 fold of the TPPS aggregates. 31 It has been reported that in tryptophan chiral L-or D-isomers solutions, the chirality of the TPPS aggregates always follows the chiral molecules and the TPPS aggregates form Lor D-helix respectively.…”
Section: Resultsmentioning
confidence: 94%
“…31 The chirality of TPPS aggregates is normally attributed to the helical formation of the TPPS aggregates due to the broken of the mirror-symmetry of the diprotonated porphyrins in the TPPS aggregates or the formation of a 90 fold of the TPPS aggregates. 31 It has been reported that in tryptophan chiral L-or D-isomers solutions, the chirality of the TPPS aggregates always follows the chiral molecules and the TPPS aggregates form Lor D-helix respectively. 45 Moreover, the chirality of the TPPS J-aggregates in the complex L-or D-Trp multiplayer films formed via ex situ also follows the chirality of films.…”
Section: Resultsmentioning
confidence: 99%
“…There has been considerable interest in the possibility that vortex motion in a conical swirl might be exploited to induce absolute enantioselection, but until recently no convincing example has been demonstrated experimentally [67]. Then -several years ago reports appeared of mirror-symmetry breaking in homoassociation of achiral diprotonated porphyrins where helical conformations were generated by stirring in a rotary evaporator with the sense of chirality, detected by circular dichroism, being selected by the sense of stirring [70,71]. In a later report, the same group claimed to have achieved similar results through magnetic stirring in a small tube, and went on to provide an explanation in terms of hydrodynamic effects of the vortex at the walls of the container [72].…”
Section: Truly Chiral Influencesmentioning
confidence: 99%